Disease cycle of Austropuccinia psidii on Eucalyptus globulus and Eucalyptus obliqua leaves of different rust response phenotypes - Yong, Wilson Thau Lym; Peter. K. Ades; Josqin. F. Tibbits; Gerd Bossinger; Fatima Akter Runa; Karanjeet S. Sandhu; Paul W. J. Taylor (2019)
Myrtle rust poses a signiﬁcant biosecurity threat to Australia with potential for long-term damaging impacts on nativeﬂora and plant industries. This study describes the disease cycle of Austropuccinia psidii, the myrtle rust pathogen, in Eucalyptus globulus and Eucalyptus obliqua, two commercially and ecologically important species from different sub-genera of Eucalyptus. Ontogeny and morphology of infection structures of A. psidii on plants of both Eucalyptus species with different rust response phenotypes, i.e. completely resistant, hypersensitive and highly susceptible, were investigated. Plants were inoculated with single-uredinium-derived urediniospores and examined by scanning electron microscopy. No differences between rust response phenotypes were observed in germination of urediniospores, formation of appressoria or length of germ tubes. The growth of germ tubes had no afﬁnity towards stomata of either species. Histological observations indicated direct penetration by infection pegs through the leaf cuticle and no penetration beyond the epidermis on rust-resistant E. obliqua.Eucalyptus obliqua plants that were identiﬁed as susceptible to A. psidii at 3- and 6-months-old showed no disease when reinoculated with A. psidii at 12-months-old; this indicated possible early acquisition of adult plant resistance to A. psidii in this species. In the susceptible phenotype of E. globules rust inoculation led to rapid colonization of leaf parenchyma cells with the disease cycle completed within 10 days. These ﬁndings provide valuable insights into host–pathogen interactions in the Eucalyptus–A. psidii pathosystem,which might be useful for the development of effective rust control strategies across Eucalyptus subgenera.